Pertumbuhan dan Hasil Kacang Hijau (Vigna radiata, L.) pada Beberapa Dosis Pupuk Organik dan Kerapatan Tanam - Hastuti, Desi Putri; Supriyono, Supriyono; Hartati, Sri (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Mungbean is one of the strategic annual food crops that needed by Indonesian people because of the high protein and minerals. Production of mungbean in Indonesia always decreases. Cultural improvements are needed to increase productivity i.e by appropriate fertilization and plant density. The experiment objective was to find out the optimum dosage of organic fertilizer and plant density for the growth and yield of mungbean. The experiment was carried out using factorial completely randomized design (CRD). The first factor treatments were organic fertilizer which consisted of 0, 5, 10, 15, and 20 ton ha-1, while the second-factor treatments were planted density which consisted of 1 and 2 plants in the hole. Organic fertilizer of 5 ton ha-1 gave the best result for plant height, number of branches, flowering age, number of pods, fresh weight and dried straw, weight of 100 seeds, number and weight of seeds, small of seeds number and P nutrient uptake of the plant. The 2 plants per hole gave the best result for branches number, pods number and number of small seeds. Application of 5 ton ha-1 organic fertilizer and 1 plant per hole gave better yield. No interaction of organic fertilizer and plant density to mungbean growth and yield.